2022
DOI: 10.23822/eurannaci.1764-1489.219
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-10-1082G > A, -819C > T and -592C > A Polymorphisms with susceptibility to asthma in children: a Systematic Review and Meta-Analysis

Abstract: Studies evaluating the association of IL-10 polymorphisms with risk of pediatric asthma found inconsistent data. Here, we performed a meta-analysis to get a precise estimation of the associations. Relevant studies identified in the PubMed, Scopus, CNKI databases were used to perform a metaanalysis. A total of 23 case-control studies including nine studies with 1298 cases and 1079 controls on -1082G>A, four studies with 622 cases and 603 controls on -819C>T and ten studies with 1480 case and 1462 controls on -5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Our results were also in partial agreement with the previous meta‐analysis by Huang et al, 37 which demonstrated no overall relationship between the rs1800896 and pediatric asthma risk, but a significant association in Asians under the dominant model and in non‐Asians under the recessive model, based on data from 1436 cases and 1112 controls. Another recent meta‐analysis by Dastgheib et al, 38 which included 1298 cases and 1079 controls, also showed no statistical significance for the association between polymorphism and pediatric asthma risk. However, a subgroup analysis based on the ethnic group showed a significant association between polymorphism and pediatric asthma risk in Asians in the homozygous model 38 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our results were also in partial agreement with the previous meta‐analysis by Huang et al, 37 which demonstrated no overall relationship between the rs1800896 and pediatric asthma risk, but a significant association in Asians under the dominant model and in non‐Asians under the recessive model, based on data from 1436 cases and 1112 controls. Another recent meta‐analysis by Dastgheib et al, 38 which included 1298 cases and 1079 controls, also showed no statistical significance for the association between polymorphism and pediatric asthma risk. However, a subgroup analysis based on the ethnic group showed a significant association between polymorphism and pediatric asthma risk in Asians in the homozygous model 38 …”
Section: Discussionmentioning
confidence: 94%
“…Another recent meta‐analysis by Dastgheib et al, 38 which included 1298 cases and 1079 controls, also showed no statistical significance for the association between polymorphism and pediatric asthma risk. However, a subgroup analysis based on the ethnic group showed a significant association between polymorphism and pediatric asthma risk in Asians in the homozygous model 38 …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Matters can become even more complicated when certain polymorphisms are related to allergic diseases in some ethnicities and not in others (maybe due to environmental factors related to those ethnicities). For instance, Dastgheib et al ( 28 ) performed a stratified meta-analysis on the association between certain polymorphisms of the IL-10 gene and pediatric asthma. Although their main conclusion was that none of these (IL-10-1082G > A, −819C > T, or −592C > A) were associated with asthma in the overall population, there was a significant association of IL-10-1082G > A with pediatric asthma in Asian and Chinese populations.…”
Section: Geneticsmentioning
confidence: 99%
“…Respiratory allergic diseases like asthma and rhinitis frequently start in childhood. The specific contribution of genetics to their pathogenesis has been highlighted by many studies in the last decade ( 4 9 ). We have recently proposed a multi-factorial model characterized by a complex interplay between genes and environment ( 10 ).…”
Section: Introductionmentioning
confidence: 99%